A Homoleptic Beryllium Carbonyl Complex with an End‐On and Side‐On Bridging Carbonyl Ligand. (16th November 2020) - Wang, Guanjun; Zhou, Yangyu; Jin, Xiaoyang; Jin, Jiaye; Zhou, Mingfei
Abstract: Homoleptic dinuclear beryllium carbonyl cation complexes have been produced and characterized in the gas phase. Infrared photodissociation spectroscopic and theoretical results confirm that Be2 (CO)5 + is a coordination saturated complex that can be assigned to a mixture of two almost isoenergetic structural isomers. Besides a beryllium–beryllium single‐bonded (OC)2 Be‐Be(CO)3 + isomer, another structure involving an unusual end‐on and side‐on bridging carbonyl ligand with very low carbonyl stretching frequency is identified. Abstract : Infrared photodissociation spectroscopic and theoretical studies show that the coordination‐saturated Be2 (CO)5 + cation prefers to form the structure involving an unusual end‐on and side‐on bridging carbonyl ligand with very low carbonyl stretching frequency.